Evaluasi Penerapan Pembelajaran Daring pada SMK Negeri 7 Malang dengan Model Evaluasi CIPP (Context, Input, Process, Product) - Syinthia Dwi Fortuna; Satrio Hadi Wijoyo; Admaja Dwi Herlambang (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
The circular letter No. 4 of 2020 of the Ministry of Education and Culture regarding education policies during the Covid-19 pandemic contains appeals for implementing online learning. This condition leads to the evaluation of the application of online learning at State Vocational High School 7 Malang that has never implemented online learning before. Learning evaluation is useful to determine the achievement of learning objectives. This study aims to evaluate the application of online learning programs at State Vocational High School 7 Malang using the CIPP (Context, Input, Process, Product) evaluation model. It is expected that the study can provide information for State Vocational High School 7 Malang to improve the quality of learning programs. This study covered evaluation results based on the aspects of context, input, process, and product which in each aspect provided information about the implementation of online learning programs at this school and the influencing factors.